Quality of life in children with food allergies, psychiatric symptoms, and caregiving burden of their mothers - Kilic, Nulufer; Kaya, Suheda; Tasci, Gulay; Ozsoy, Filiz; Kilic, Mehmet (Codon Publications, 2023)
Objective: The present study aimed to evaluate the quality of life in children with food allergies, the accompanying depression and anxiety disorders, and caregiving burden of their mothers. Material and Methods: A total of 168 children with food allergy visiting our clinic and their mothers were included in the study group. The control group included 152 children who visited the healthy child follow-up clinic of our hospital and their mothers. Studying mothers' opinions, the Food Allergy Quality of Life Questionnaire Parent Form (FAQLQ-PF) was used for evaluating children, and the Beck's Depression Inventory, Beck's Anxiety Inventory, Temperament Evaluation of Memphis, Pisa, Paris, San Diego Auto-questionnaire, and Zarit Caregiver Burden Scales were used for evaluating mothers. Results: No differences were noticed between the study and control group regarding mean age and gender distribution (P > 0.05). In the study, the FAQLQ-PF total and subscale scores of children with food allergies were determined according to the opinions of their mothers, and scores tended to increase with age (P < 0.0001). In addition, it was determined that mothers of children with food allergies had higher levels of anxiety, depression, and caregiving burden than mothers of the control group (P < 0.0001). Conclusion: In order to develop a multidisciplinary approach for children with food allergies, we conceived as appropriate to inform their families about the difficulties of caregiving and psychosocial disorders that could develop over time. They also must be informed to take preventive measures as well as the medical aspects of their children's disease. (c) 2023 Codon Publications. Published by Codon Publications.
Keywords: anxiety; burden of care; depression; food allergy; quality of life